The Effect of Constructivism Learning Approach on Students' Mathematics Learning Outcomes in Material Relations and Functions of Grade VIII SMP Negeri 11 Pematangsiantar - Sidabutar, Ropinus; Napitupulu, Salmen; Sauduran , Golda Novatrasio (Lembaga Riset Mutiara Akbar, 2023)
he purpose of this study was to determine whether there was an effect of the influence of the constructivist learning approach on the mathematics learning outcomes of class VIII students of SMP Negeri 11 Pematangsiantar. The method used in this study is a quantitative research method Quasi Experimental Design. The results of the instrument test analysis showed that the instrument was valid and reliable, in addition to the results of the calculation of the data analysis, it was obtained that the sample was normally distributed and homogeneous. The hypothesis of this research is that there is an effect of the influence of the constructivist learning approach on the mathematics learning outcomes of class VIII students of smp negeri 11 pematang siantar. Based on the results of calculations using the t test, it is found that is 5.906 and is 2.01537, because > is 5,906 > 2,01537 so is accepted and is rejected, meaning that there is an influence of the influence of the constructivist learning approach on the mathematics learning outcomes of class VIII students of smp negeri 11 pematang siantar. The results of this study are expected to be useful for related parties such as teachers, students and further researchers